Bilingual young learners "read" their picturebooks: a multidimensional research in Greece - І. Пападопулос І.; Н. Кошарна (Borys Grinchenko Kyiv Metropolitan University, 2023)
In the current research, the reactions of young learners, who come from a migrant background, are investigated in connection to their involvement with picturebooks. In order to accomplish this goal, a sample group consisting of fifty children aged five years old who were L1 speakers in Albanian and Bulgarian and were receiving their preprimary education in Greece was chosen to take part in this research study. The children's interactions with a picture book were watched by their instructors while it took place in front of them in the classroom. The study put an emphasis on providing analytical replies relevant to the following four major areas: a) Narrative Meaning; b) Illustrations; c) Context of Book Development; and d) Linguistic Codes. According to the findings of the research, pupils take an active role in their interactions with picture books. As a consequence of this, suggestions have been made for the conduct of more study and the use of educational practices.